2008
DOI: 10.1021/bm800300b
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FT-IR Microscopic Study on Enzymatic Treatment of Poplar Wood Cross-Sections

Abstract: The feasibility of Fourier transform infrared (FT-IR) microscopy to monitor in situ the enzymatic degradation of wood was investigated. Cross-sections of poplar wood were treated with cellulase Onozuka RS within a custom-built fluidic cell. Light-optical micrographs and FT-IR spectra were acquired in situ from normal and tension wood fibers. Light-optical micrographs showed almost complete removal of the gelatinous (G) layer in tension wood. No structural and spectral changes were observed in the lignified cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 57 publications
9
95
0
Order By: Relevance
“…Bands from 950-1200 cm -1 are mainly carbohydrates (Bui et al 2015). The PC2 loading exhibited strong positive signals at 1060 and 1034 cm -1 (Figure 4c), the bands of which are specific to C-O stretching vibrations related to polysaccharides (Pandey 1999, Gierlinger et al 2008, whose assignments on carbohydrate are summarised in Table 2. Score plots and PC2 loading, obtained from the finger print region, demonstrated that fibres located close to the vessel tended to have less sugars compared to those distant from the vessel.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Bands from 950-1200 cm -1 are mainly carbohydrates (Bui et al 2015). The PC2 loading exhibited strong positive signals at 1060 and 1034 cm -1 (Figure 4c), the bands of which are specific to C-O stretching vibrations related to polysaccharides (Pandey 1999, Gierlinger et al 2008, whose assignments on carbohydrate are summarised in Table 2. Score plots and PC2 loading, obtained from the finger print region, demonstrated that fibres located close to the vessel tended to have less sugars compared to those distant from the vessel.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…White rot decay was shown to be evenly distributed within secondary cell walls of tracheids. Gierlinger et al (2008) used Raman microspectroscopy to study in situ enzymatic degradation of poplar wood cell walls within a custom-built fluidic cell. They found that as the set-up continuously provided fresh highly concentrated cellulases, cellulose accessibility was the limiting factor and thus the G-layers of tension wood were degraded considerably faster than normal wood cell walls.…”
Section: Cell Wall Degradationmentioning
confidence: 99%
“…Time of flight secondary ion mass spectroscopy (Jeremic et al 2014), infrared absorption (Gierlinger et al 2008) and Raman scattering techniques (Gierlinger and Schwanninger 2006) allow studying chemical information at submicrometre spatial resolution. Imaging speed of micro-spectroscopy techniques is often limited by the amount of spectral information one wants to retrieve.…”
Section: Introductionmentioning
confidence: 99%